Cell‐Penetrable Lysine Dendrimers for Anti‐Cancer Drug Delivery: Synthesis and Preliminary Biological Evaluation. Issue 7 (17th April 2014) - Zhao, Jing; Zhou, Rui; Fu, Xiaoyu; Ren, Wen; Ma, Lifang; Li, Ran; Zhao, Yi; Guo, Li
<x xml:space="preserve">Abstract</x> Improving the cell penetration and enhancing the cell selectivity of drugs have been approved for overcoming the major drawbacks of chemotherapeutic agents: the toxicity to normal cells and the drug resistance in tumors. In this paper, lysine dendrimers (G1–G3) were chosen as novel cell‐penetrating carriers for anti‐cancer drugs based on the internalization mechanism of cell‐penetrating peptides and the characteristics of dendritic peptides. After labeling with fluorescein isothiocyanate (FITC), the cell‐penetrable capacity of lysine dendrimers was certified by flow cytometric analysis. In a preliminary biological evaluation, the conjugates of lysine dendrimers and 5‐fluorouracil showed the expected advantages: stable drug release, low toxicity to normal cells, and moderate inhibition of tumor cells. These results imply that cell‐penetrable lysine dendrimers could be potential carriers in drug delivery of anti‐cancer medicine.